The Key Elements of the Draft Treaty Establishing Northeast Asia Nuclear-Weapon-Free Zone - Kaneko, Kumao (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.23 Mongolian Journal of International Affairs No.14 2007 pp.51-57